PENGARUH DOSIS PUPUK KANDANG AYAM DAN PEMBERIAN DEKOMPOSER MIKROORGANISME TERHADAP PERTUMBUHAN DAN HASIL KENTANG (Solanum tuberosum, L.) VARIETAS GRANOLA - WARYANTO WARYANTO; TEGUH SUPRIYADI; AGUS BUDIONO (JURNAL ILMIAH AGRINECA, 2012)
This research purpose to know dosage of chiken stable manure and effective microorganisme (EM4) towards growth and result of potato. The hipotesis was dosage of chiken manure 10 ton/ha with effektuive microorganisme 10 ton/ha will take growth and yield the best. This research was cariied out in Pandansari, Paguyangan, Brebes. The heigent place of 1700 dpl, with latosol soil type. This resear birth was done from Juli-September 2011. The research meteode was factorial with Randomized Completly Block Design (RCBD), consist of two factors, that was : 1). Dosage of chiken stables manure (K) with 3 levels, that was : 5 ton/ha, 10 ton/ha and 15 ton/ha. 2). Dosage of effektive microorganism with 3 levels, that was: 0 l/ha, 5 l/ha, and 10 l/ha. The result of this research was 1) Dosage of chiken stable manure was significant to weight of tube, sum of branchdry weight crop, height of plant, sume of stem, sum of leaf and diameters ofÂ  tube. 2) dosage of effective microorganism was signiticant to sum of branch and sum of leaf. 3) interaction about dosage of chiken stable manure and effektive microorganism was significant to dry weight crop. 4) the best yield on dosage of chiken stable manure 10 ton/ha.